Pengaruh Pengetahuan Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus pada Wajib Pajak di Samsat Kota Bandung) - Valentina Caroline Swanto Putri; Vinny Stephanie Hidayat (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2023)
This study seeks to demonstrate how knowledge of tax and tax sanctions affects compulsory tax compliance with motor vehicle tax laws. The research method used is the quantitative research method, which means that the population in this study is all taxable and registered in SAMSAT Pajajaran Bandung. Sampling techniques in this study use nonprobability sampling using purposive sampling. In the process, 60 respondents were collected as samples of research data collected through questionnaires. The instruments of this research are taxation knowledge, tax sanctions, and tax compliance. In data analysis, we used double regression analysis. Based on the findings, it can be concluded that tax knowledge and tax sanctions positively affect tax compliance.